Exploration of the Effect of Carbon Fiber Ratio and Dimensions on Electrical Conductivity in Mortars - UZUNALİOĞLU, Hacer; YAZICIOĞLU, Salih; AHISKALI, Adem; ÇAĞLAR, Hakan (Kirsehir Ahi Evran University, 2022)
This study was carried out on Class F and C fly ash reinforced, carbon fiber added mortar samples as a substitute for PÇ42,5 cement. Carbon fiber was added in different sizes at rates of 0.5%, 1%, and 3% in order to investigate the effects of the size and ratio of carbon fiber on electrical conductivity. 33 different series were formed such as obtained Class F; without fly ash 10%, 20% and Class C; without fly ash, 10%, 20% with samples without carbon fiber and with carbon fiber having dimensions 5 mm and 10 mm. The water/cement ratio was prepared to take the value of 22-23cm in the flow table test.,A viscosity regulator of 0.1% of the fine material was used in order to ensure homogeneous distribution of carbon fiber in the mortar. 3 samples were prepared for each series in order to reduce the margin of error. Electrical conductivity, compressive and tensile strength tests were applied to the oven dry and naturally moist conditions of the samples that completed their 7, 28 and 56 days curing periods. Increasing the carbon fiber size increased the tensile strengths and increasing the carbon fiber ratio increased the tensile strengths. It has been observed that carbon fiber increases the electrical conductivity, but the conductivity decreases depending on time, and as the sizes and proportions of the carbon fiber fibers increase, the compressive strength decreases due to the void effect in the mortar, while the compressive strength increases with the increase in the fly ash ratio. The microstructure and carbon fiber distribution of the samples were examined using SEM (Scanning Electron Microscopy) and it was seen that the carbon fiber distribution was in a way that supports the electrical conductivity measurement. The study allowed the size and proportion effect of carbon fiber in mortars to be compared with C and Class F reinforced mortar samples.
Keywords: Carbon fiber; Class F fly ash; Class C fly ash; Electrical conductivity; Karbon fiber; F Sınıfı uçucu kül; C Sınıfı uçucu kül; Elektriksel iletkenlik; Karbon fiber; F Sınıfı uçucu kül; C Sınıfı uçucu kül; Elektriksel iletkenlik